The Haunted Hotel - Dithmer, Monna (Peripeti, 2016)
There is something about the bodies at Hotel Pro Forma, something mysteriously elusive and unassailable. They appear with a cool remoteness and an insistent presence. They look directly at us, and they confront us. It is striking how many of the performances are explicitly set in the transitional zone between life and death as an exploration of another form of existence. Hotel Pro Forma is populated by a multitude of living dead, apparently dead, or dreamlike existences, none of which would seem to belong either here or in the beyond, but which insist on haunting the stage.